Effects of DARPP-32 Genetic Variation on Prefrontal Cortex Volume and Episodic Memory Performance - Persson, Ninni; Persson, Jonas; Lavebratt, Catharina; Fischer, Håkan (Frontiers in Neuroscience, 2017)
Despite evidence of a fundamental role of DARPP-32 in integrating dopamine and glutamate signaling, studies examining gene coding for DARPP-32 in relation to neural and behavioral cor-relates in humans are scarce. Post mortem findings evidence genotype specific expressions of DARPP-32 in the dorsal frontal lobes. We therefore investigated the effects of genomic variation in DARPP-32 coding on frontal lobe volumes and episodic memory. Volumetric data from the dorsolateral (DLPFC), and visual cortices (VC) were obtained from 61 younger and older adults (♀54%). The major homozygote G, T or A genotypes in single nucleotide polymorphisms (SNPs: rs879606; rs907094; rs3764352), at the DARPP-32 regulating PPP1R1B gene influenced frontal gray matter volume and episodic memory (EM). Homozygous carriers of allelic variants with lower DARPP-32 expression had overall larger prefrontal volumes, in addition to greater EM recall accuracy. The SNPs did not influence VC volume. The genetic effects on DLPFC were greater in younger adults, and selective to this group for EM. Our findings suggest that genomic variation maps on to individual differences in frontal brain volumes, and cognitive functions. Larger DLPFC volumes were also related to better EM performance, suggesting that gene-related differences in frontal gray matter may contribute to individual differences in EM. These results need further replication from experimental and longitudinal reports to determine directions of causality.